1977
DOI: 10.1136/jnnp.40.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic cataplexy.

Abstract: SUMMARYThe case is described of a man who developed attacks of cataplexy, narcolepsy, and sleep paralysis because of a microglioma which infiltrated the walls and floor of the IlIrd ventricle and the upper brain stem. The mechanisms by which the pathology is related to the symptoms are discussed.In 1880 Gdlineau coined the term 'narcolepsy' and related the clinical details of two patients who suffered from the condition, acknowledging that an account of the first had been published by Caffe in 1862. Henneberg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Niemann-Pick's disease (Kandt et al, 1982). cerebral tumors (Ethelberg, 1949;Anderson & Salmon, 1977: Stahl et al. 1980Smith, 1983).…”
Section: Multiple Sclerosis and Cataplexymentioning
confidence: 97%
“…Niemann-Pick's disease (Kandt et al, 1982). cerebral tumors (Ethelberg, 1949;Anderson & Salmon, 1977: Stahl et al. 1980Smith, 1983).…”
Section: Multiple Sclerosis and Cataplexymentioning
confidence: 97%
“…Animal studies have demonstrated a prominent role of the brain stem and hypothalamus in the regulation of sleep and wakefulness and have led to the identification of neural generators and modulators of REM sleep in the dorsolateral pons and medial medulla oblongata [2,18,27,30,32,36]. In man, several case studies have reported symptomatic narcolepsy following acquired diencephalic lesions [3,29,34] and brain stem lesions of midbrain [4,10,23,37], pontine [23,24,31,33] and medullary [8] location. However, not all of these cases exhibited a classic narcoleptic syndrome, and some did not meet all diagnostic criteria of narcolepsy according to the International Classification of Sleep Disorders (ICSD).…”
Section: Introductionmentioning
confidence: 99%
“…The craniopharyngioma develops from remnants of the embryonal hypophyseal-pharyngeal duct, located in the vicinity of the hypothalamus, the pituitary stalk and the optic chiasm. It has been known for long time that this area is important for the regulation of sleep and diurnal rhythms (17), and sleep disturbances secondary to tumors close to the hypo-thalamus and the 3rd ventricle have been repeatedly described (1,10,12,27,32). The suprachiasmatic nuclei (SNC), situated bilaterally just above the optic chiasm, act as endogenous regulators of the biological rhythm, receiving different signals directly from the optic tract (16,24).…”
Section: Introductionmentioning
confidence: 99%